2013
DOI: 10.1002/jat.2964
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of edaravone against neomycin‐induced ototoxicity in zebrafish

Abstract: Aminoglycosides such as neomycin are one of the most commonly prescribed types of antibiotics worldwide. However, these drugs appear to generate free radicals within the inner ear, which can result in permanent hearing loss. We evaluated the effects of edaravone, a neuroprotective agent, on neomycin-induced ototoxicity in transgenic zebrafish. The 5-day post fertilization (dpf) zebrafish larvae were exposed to 125 μM neomycin and various concentrations of edaravone for 1 h. Hair cell survival was calculated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Sodium selenite (Selenase; sodium selenite pentahydrate 1.66 mg/10 ml) was purchased from Biosyn Arzneimittel GmbH (Fellbach, Stuttgart, Germany). We previously reported that neuromasts treated with 125 μM neomycin for 1 h exhibited a viability of 50%, thus a dose of 125 μM neomycin was chosen as an adequate experimental concentration for the current study [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sodium selenite (Selenase; sodium selenite pentahydrate 1.66 mg/10 ml) was purchased from Biosyn Arzneimittel GmbH (Fellbach, Stuttgart, Germany). We previously reported that neuromasts treated with 125 μM neomycin for 1 h exhibited a viability of 50%, thus a dose of 125 μM neomycin was chosen as an adequate experimental concentration for the current study [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The larvae were then washed with the embryo medium three times. Zebrafish larvae were anesthetized using tricaine (3-aminobenzoic acid 0.4 g/ethyl ester; 100 mL; pH 7, adjusted using Tris buffer) for 5 min as described elsewhere [ 28 , 29 ]. The zebrafish were mounted using methylcellulose on a depression slide for evaluation under a fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zebrafish are a robust model for investigating ototoxicity and regenerative mechanisms. In this model, edaravone, a potent free radical scavenger, attenuates apoptosis and approximately doubled the number of surviving hair cells when administered concurrently with ototoxic levels of neomycin or cisplatin (Hong et al, 2013; Choi et al, 2014b). Similarly, trimetazidine, an anti- ischemic agent typically used to treat angina pectoris, is also known to reduce oxygen-derived free radicals and exhibited a three-fold attenuation of neomycin-induced hair cell loss in zebrafish (Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%